CUSTOMER SATISFACTION TOWARDS AYURVEDIC HEALTH CARE PRODUCT: A STUDY WITH REFERENCE UDUPI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Ayurveda is a medical system that deals not only with the body but with the mind and spirit as well. According to Ayurveda, most diseases connected with the psycho-physiological and pathologic changes in the body are caused by imbalance in three different dosha (i.e vata,pitta and kapha). The fundamental aim of ayurvedic therapy is restore the balance between these three major body systems. The object of this research survey is to study consumer behavior in consuming or purchasing ayurvedic products and their attitude towards herbal medicine in Udupi district. Consumers look for healthy products along with the quality because in modern India there is a great awareness about the healthy life style.